Utilization of YouTube Videos to Foster Moral Knowledge in Pancasila and Citizenship Education Learning - Katty, Katrina; Handayani, Nur Fitri; Marwiah, Marwiah; Herliah, Endang (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to describe students' responses to the use of YouTube videos in Citizenship Education learning and to examine the contribution of this medium in fostering an understanding and application of cooperative values. The research approach employed is a descriptive qualitative method, utilizing data collection techniques that include observation, interviews, documentation, and analysis of student worksheets. The subjects in this study consisted of 27 ninth-grade students at SMPN 11 Samarinda who were grouped into four discussion groups. The research findings indicate that most students responded positively to the use of YouTube videos. They consider the presentation of material through this media to be more interesting, easy to understand, and directly related to everyday life. In addition to improving students' understanding of Citizenship Education, videos also play a role in shaping their moral attitudes, particularly the value of cooperation. This is reflected in group cooperation activities, the equal division of tasks, and the behaviour of helping one another, both when studying and in activities such as class duty. Thus, YouTube is a potential medium for applying contextual and interactive learning, especially in instilling Citizenship Education values in a more meaningful way.